Kecerdasan Spiritual dalam Konteks Pengajaran Kristen: Memahami Efek Pencerahan Rohani melalui Narasi Efesus 1:17-18 - Leiwakabessy, Tabita; Purwonugroho, Daniel Pesah (MANTHANO: Jurnal Pendidikan Kristen, 2024)
Abstract: Spiritual intelligence is an intelligence highly needed by learners. Spiritual intelligence is the highest intelligence, and it can shape the personality, motivation, and mental strength of learners. From a Christian faith perspective, spiritual intelligence can be nurtured through Biblical narratives as teaching material. Ephesians 1:17-18 is a teaching material that can enhance learners' spiritual intelligence. This teaching material is also delivered through storytelling technique. Storytelling is a teaching technique to make learners experience imaginative effects and enable them to extract values from the teaching material without feeling lectured. Storytelling heavily relies on the competence of the teacher. Teachers can combine storytelling with various tools to create imaginative effects so that learners' spiritual intelligence can be achieved. Using a qualitative-descriptive method, the author concludes that Ephesians 1:17-18 is the appropriate teaching material to be presented through storytelling to enhance learners' spiritual intelligence. Ephesians 1:17-18 narrates how the Ephesian church realizes their existence in Jesus, which leads them to experience spiritual enlightenment and have an impact on their personal lives. The same can happen to learners if Ephesians 1:17-18 is applied through storytelling to enhance each learner's spiritual intelligence. Abstrak: Kecerdasan spiritual adalah kecerdasan yang sangat dibutuhkan peserta didik. Kecerdasan spritiual adalah kecerdasan tertinggi dan kecerdasan spiritual dapat membentuk kepribadian, motivasi dan kekuatan mental peserta didik. Dalam perspektif iman Kristen, kecerdasan spiritual dapat dibentuk dengan kisah Alkitab sebagai materi ajar. Efesus 1:17-18 adalah materi ajar yang dapat meningkatkan kecerdasan spiritual peserta didik. Materi ajar tersebut juga disampaikan dengan teknik story-telling. Story-telling adalah sebuah teknik mengajar untuk membawa peserta didik mengalami efek imajinatif dan membuat peserta didik dapat mengambil value yang berasal dari bahan ajar tanpa merasa digurui. Story-telling sangat amat bergantung dengan kompetensi pengajar. Pengajar dapat menggabungkan story-telling dengan berbagai alat untuk menciptakan efek imajinatif agar kecerdasan spiritual peserta didik dapat dicapai. Dengan menggunakan metode kualitatif-deskriptif,  penulis menyimpulkan bahwa Efesus 1:17-18 adalah bahan ajar yang tepat untuk dibawakan secara story-telling demi meningkatkan kecerdasan spiritual peserta didik. Efesus 1:17-18 menceritakan tentang bagaimana jemaat Efesus menyadari keberadaan mereka di dalam Yesus yang membuat jemaat Efesus mengalami pencerahan spiritual dan memberikan dampak dalam kehidupan pribadi masing-masing. Hal tersebut juga dapat terjadi kepada peserta didik apabila menerapkan Efesus 1:17-18 dengan story-telling untuk meningkatkan kecerdasan spiritual masing-masing peserta didik.